The Role of the Implementation of the Regional Government Information System (SIPD) in Achieving Regional Financial Performance Through the Efficiency of Regional Financial Management - Sahabudin Sahabudin; Andi Chairil Furqan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Effective regional financial performance reflects efficient financial management supported by an integrated information system. This study aims to examine the effect of regional financial management efficiency on regional financial performance, with the implementation of the Regional Government Information System (SIPD) as a mediating variable. A quantitative approach was employed, involving 229 respondents from Regional Apparatus Organizations (OPD). Data were analyzed using multiple linear regression and moderation tests. The results indicate that regional financial management efficiency significantly affects regional financial performance. Furthermore, the implementation of SIPD was found to moderate the relationship between these variables. These findings highlight the importance of utilizing information technology to enhance accountability and effectiveness in regional financial management. The study is limited by its regional scope and the quantitative method applied. Therefore, future research is recommended to adopt a mixed-method approach and include a broader regional coverage to obtain more comprehensive results.